2019
DOI: 10.1155/2019/9142753
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Tomato Disease Types and Detection of Infected Areas Based on Deep Convolutional Neural Networks and Object Detection Techniques

Abstract: This study develops tomato disease detection methods based on deep convolutional neural networks and object detection models. Two different models, Faster R-CNN and Mask R-CNN, are used in these methods, where Faster R-CNN is used to identify the types of tomato diseases and Mask R-CNN is used to detect and segment the locations and shapes of the infected areas. To select the model that best fits the tomato disease detection task, four different deep convolutional neural networks are combined with the two obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(60 citation statements)
references
References 25 publications
0
43
0
2
Order By: Relevance
“…Also, some studies combine the Mask R-CNN framework with object detection networks for plant diseases and pests detection. Wang et al [ 83 ] used two different models, Faster R-CNN and ask R-CNN, in which Faster R-CNN was used to identify the class of tomato diseases and Mask R-CNN was used to detect and segment the location and shape of the infected area. The results showed that the proposed model can quickly and accurately identify 11 class of tomato diseases, and divide the location and shape of infected areas.…”
Section: Plant Diseases and Pests Detection Methods Based On Deep Leamentioning
confidence: 99%
“…Also, some studies combine the Mask R-CNN framework with object detection networks for plant diseases and pests detection. Wang et al [ 83 ] used two different models, Faster R-CNN and ask R-CNN, in which Faster R-CNN was used to identify the class of tomato diseases and Mask R-CNN was used to detect and segment the location and shape of the infected area. The results showed that the proposed model can quickly and accurately identify 11 class of tomato diseases, and divide the location and shape of infected areas.…”
Section: Plant Diseases and Pests Detection Methods Based On Deep Leamentioning
confidence: 99%
“…In Table III, a comparison between these models and the proposed model based on average test accuracies is provided for the tomato dataset. For a fair comparison, other implementations in the literature using custom tomato datasets [12][11] [22] were not adopted for this exercise. It can be seen from Table III that the proposed model produced results that are comparable to the state-of-the-art models irrespective of the complexity of the input images.…”
Section: Comparison To Related Work In Literaturementioning
confidence: 99%
“…Wang et al [22] collected sick tomato leaf images from the internet and trained a region-based CNN (R-CNN) to detect disease types and areas of infection. Their networks were so deep that ResNet-101 obtained 23.25 hours of training time.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs allow us to develop models based on the intrinsic relations among the variables, without prior knowledge of their functional relationships [9]. Soft computing for ANN techniques has been widely used to develop models to predict different crop indicators, such as growth, yield, and other biophysical processes, and also because of the commercial importance of tomato [10][11][12][13][14][15][16][17][18][19][20][21][22][23] and other vegetables, such as lettuce [24][25][26][27][28][29][30], pepper [31][32][33][34], cucumber [35][36][37][38], wheat [39][40][41][42][43][44][45], rice [46][47][48], oat [49], maize [50,51], corn [52][53][54], corn and soybean [55], soybean…”
Section: Introductionmentioning
confidence: 99%